2002
DOI: 10.1007/bf02287837
|View full text |Cite
|
Sign up to set email alerts
|

The effect of technical support on clinician attitudes toward an outcome assessment instrument

Abstract: This study evaluated the impact of technical support on mental health clinicians' attitudes and use of an outcome assessment (OA) instrument. Technical support involved providing clinicians with the scored and profiled results of an OA instrument administered to their patients. It was predicted that temporary exposure to the instrument's uses would improve clinicians' attitudes toward the instrument and that improved attitudes would lead to greater use. The results indicated that subsequent to support clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
14
2
Order By: Relevance
“…Collectively, results of a series of studies suggest that implementation of MBC in mental health may be facilitated by initial training – and can be sustained with additional consultation – but that a “decline effect” is apparent without continued contact (e.g., Close-Goedjen and Saunders, 2002; De Rond, De Wit, & Van Dam, 2001). A recent evaluation of a state-wide training and consultation program for child and family mental health clinicians found early increases in positive assessment attitudes, with more gradual increases in self-reported skill and use(Lyon, Dorsey, Pullmann, Silbaugh-Cowdin, & Berliner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, results of a series of studies suggest that implementation of MBC in mental health may be facilitated by initial training – and can be sustained with additional consultation – but that a “decline effect” is apparent without continued contact (e.g., Close-Goedjen and Saunders, 2002; De Rond, De Wit, & Van Dam, 2001). A recent evaluation of a state-wide training and consultation program for child and family mental health clinicians found early increases in positive assessment attitudes, with more gradual increases in self-reported skill and use(Lyon, Dorsey, Pullmann, Silbaugh-Cowdin, & Berliner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Generally positive attitudes to OM but uncertainty as to how to use the results were found by Meadows et al (1998) in relation to diabetes care. In a mental health setting, Close-Goedjen and Saunders (2002) found that provision of technical support improved clinicians' attitudes. Worryingly, however, attitudes remained high but behaviour returned to initial levels after support was withdrawn, leading them to conclude that ''.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with previous research findings where the provision of technical support led to more positive attitudes toward outcome measures among clinicians. 5 Questionnaire results also revealed that most staff preferred information presented in graphical format over text or numbers. The fact that many of the changes were maintained, and even in some cases extended, at follow-up, suggests that the intervention was not simply effective while it lasted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that provision of technical support enhanced the use of data by clinicians. 5 The QUATRO North East project team wanted to learn more about whether the provision of further guidance to mental health clinicians and team leaders improved their understanding of what ROM results mean and of how these results could be used to inform clinical practice. Of particular interest would be the information pertaining to changes in a consumer' s health over time and at different collection occasions.…”
Section: What Are the Implications?mentioning
confidence: 99%